The magic of turquoise - Khālid, Mayy (Modern Arabic literature., 2011)
Was Nirvana's near-fatal accident at sea simply a case of bad timing, or was it attempted suicide? And what was so important about an unread email that made her jump recklessly into the Mediterranean? As Leila tries to make sense of her aunt's fate, Nirvana embarks on a journey through memories and secrets. Leila guiltily questions her own fears and failures, bearing the blame of a family that curses the day she was born. Lying in a coma, Nirvana's story of choices made and roads not taken paint a colorful picture of her struggle against expectations in 1980s Egypt. The two voices are skillfully woven together to create an intricate narrative about breaking free from family tradition and the dreams that come back to haunt us. From the sunny beaches of Alexandria to the Bavarian Alps, author Mai Khaled explores the subtleties of family relationships and individual choices.